Effect of Intraoperative Loading Dose of Amiodarone for Prophylaxis Against Atrial Fibrillation in Patients with Rheumatic Valvular Heart Disease Undergoing Valve Replacement Surgery - Rahman, Romena; Rahim, AM Asif; Shahidullah, AYM; Anisujjaman, QM; Hossain, ASM Iftekher; Hasan, Md Kamrul; Raha, Sanjay Kumar (Cardiovascular Journal, 2020)
Background: Atrial Fibrillation (AF) is the most common arrhythmia occurring after cardiac surgery and its peak incidence is between second or third postoperative day. It occurs in 40% to 50% of patients after valve surgery alone or combined valve and CABG surgery respectively. Among all the anti-arrhythmic drugs evaluated for AF, amiodarone has shown the most promising results with successful conversion and maintenance of normal sinus rhythm achieved in 50%–70% of patients. Methods: Sixty diabetic patients purposively selected who underwent isolated off pump coronary artery bypass procedure in NICVD. Group A – 30 patients receiving loading dose of amiodarone intra-operatively before establishment of CPB during valve replacement surgery and Group B- 30 patients without receiving loading dose of amiodarone intra-operatively during valve replacement surgery. Incidence of atrial fibrillation in postoperative period was evaluated. Results: Atrial fibrillation was observed in 8 (26.7%) patients in group A and 18 (60%) patients in group B (p=0.009). Ventricular tachycardia developed in 6.7% patients in group B and none in group A (p=0.47). Mean duration of ICU stay was 2.04±0.30 days in Group A and Group B was 2.98±0.77 days (p=0.03). Mean duration of post-operative stay was 7.20±0.66 days in Group A and Group B was 7.85±0.60 days (p=0.10). Conclusion: A single intra operative dose of intravenous amiodarone increases the incidence of conversion of AF to normal sinus rhythm. When AF persisted, use of amiodarone reduces the frequency of need for cardioversion and the energy required for it. Cardiovasc. j. 2020; 12(2): 102-108